Two new species of the Polysphincta genus-group (Hymenoptera: Ichneumonidae: Pimplinae) reared from their spider (Araneae) hosts in Europe - Fritzén, Niclas R. (Zootaxa, 2014)
Flacopimpla barathrica sp. n. and Zatypota flamma sp. n., belonging to the Polysphincta genus-group, are described, the former from Fennoscandia and the latter from Hungary. Like other species of this group for which the natural history is known, the new species are koinobiont ectoparasitoids of spiders. They have been reared from the theridiid spiders Thymoites bellissimus (L. Koch) and Parasteatoda sp. Archer respectively. The host records support the hypothesis of Flacopimpla being parasitoids of the spider family Theridiidae. The results also indicate that F. barathrica sp. n. has a very narrow host range consisting of a single species in Fennoscandia. The genus Flacopimpla was previously only known from the New World, and F. barathrica sp. n. is thus the first species of its genus in the Palaearctic. It is also the first troglophilic species of the Polysphincta genus-group. Zatypota albicoxa (Walker) is reported as new to Hungary.